2012
DOI: 10.1590/s0034-89102012000500002
|View full text |Cite
|
Sign up to set email alerts
|

Efetividade de programa de controle de qualidade em mamografia para o Sistema Único de Saúde

Abstract: OBJECTIVE:To assess the effectiveness of a quality control program in mammography services of the Brazilian National Health System (SUS). METHODS:A prospective study using temporal analysis of a health surveillance action was conducted. A total of 35 service providers that had mammography equipment in operation and regularly performed exams between 2007 and 2009 in the state of Goiás, Central-Western Brazil, participated in this study. Services were assessed during three site visits by performance testing of m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
0
3

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 12 publications
2
13
0
3
Order By: Relevance
“…In the present study, as the production of screening mammograms was analyzed, the authors observed that 44% of the mammograms were performed on patients in the age range between 40 and 49 years, 31.7% in the age range between 50 and 59 years, and 13.2% in the age range between 60 and 69 years. Such results demonstrate that the prevalence of mammograms is not coincident with the age group with highest breast cancer incidence, and that, like in other studies, the physician-patient relationship seems to be the most significant predictor for the performance of mammography (10,32,41,42) .…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…In the present study, as the production of screening mammograms was analyzed, the authors observed that 44% of the mammograms were performed on patients in the age range between 40 and 49 years, 31.7% in the age range between 50 and 59 years, and 13.2% in the age range between 60 and 69 years. Such results demonstrate that the prevalence of mammograms is not coincident with the age group with highest breast cancer incidence, and that, like in other studies, the physician-patient relationship seems to be the most significant predictor for the performance of mammography (10,32,41,42) .…”
Section: Discussionsupporting
confidence: 74%
“…In 2010, 45 mammography apparatuses (32) were available for SUS in the state of Goiás. The present study allows inferring that one third of such apparatuses were installed in the Goiânia municipality.…”
Section: Discussionmentioning
confidence: 99%
“…Em radiodiagnóstico, este programa visa garantir que as imagens médicas produzidas pelos equipamentos possuam qualidade suficiente para que traga o correto diagnóstico com o menor custo e dose possível para profissionais e pacientes, além de manter a instalação de acordo com legislações vigentes. [6] É possível observar que no setor de radiologia onde não existe um PGQ, existem alguns problemas organizacionais, tal como a repetição de exames, descarte excessivo de películas radiográficas, desperdício de materiais, perda de exames já realizados, demora no atendimento e que podem ser resolvidos a partir do desenvolvimento de um sistema de gestão de qualidade, envolvendo toda a organização [7], o que inclusive é atribuído como de extrema importância por parte dos profissionais, de forma que a padronização de rotina e como ferramenta útil para facilitar o decorrer do exercício da função [8].…”
Section: Introductionunclassified
“…Considering the academic and clinical consensus about mammography being the imaging method of choice for breast cancer screening ( 5 ) , it is expected that such a procedure produces good-quality images with the use of the lowest possible radiation dose. In Brazil, the initiatives aimed at mammography quality assurance started in 1991, with the Mammography Quality Control Program implemented by Colégio Brasileiro de Radiologia, whose adhesion was voluntary ( 6 , 7 ) . In the same decade, the Federal Ordinance 453/98 established the guidelines for protection in medical and odontological radiodiagnosis ( 6 , 8 , 9 ) .…”
Section: Introductionmentioning
confidence: 99%